Frecuencia de Salmonella y Shigella en moscas domésticas colectadas en la ciudad de San José - Bolaños, Róger (1959)
One hundred lots of 20 house flies each were collected in the Municipal Slaughterhouse and the City Market of San Jose, Costa Rica, and in the animal room of the School of Microbiology, University of Costa Rica. Collections were made at different times through the year. Cultures showed an incidence of 24.0 per cent for Salmonella and 1.0 per cent for Shigella. No seasonal variation was detected either for frequency of organisms or for any particular serotype.